World Orders, Old and New: By Noam Chomsky. Boulder, CO: Pluto Press, 1994, pp. 272 (American Journal of Islam and Society, 1996)
The catch phrase "new world order" has shaped the view of the futuredifferently for various groups and people. It has been associated mostlywith former American president George Bush, who witnessed the end ofthe old system with the collapse of the Soviet Union and, with others, realizedthe beginning of a new order. Prior to the end of the cold war, ThirdWorld countries were calling for "new economic and political orders."Speaking before the General Assembly of the United Nations, Fidel Castrocalled for the establishment of a "new world order based on justice, onequity, on peace." And an altogether different new world order has beenanticipated in the near future by such evangelists as Pat Robertson in hisbook The New World Order. Robertson believes the new order will commencewith the rerurn of the Messiah, who will erect a new and just world.However, for prominent scholar Noam Chomsky, the new world orderis merely a continuation of the old one. From the basis of three lecturesdelivered at the American University in Cairo in May 1993, Chomskywrote World Orders, Old and New. The book is divided into three parts.The first part discusses the cold war and how it was used by the superpowersto justify all foreign and domestic political, economic, and militaryactions. “The Cold War provided easy formdas to justify criminal actionsabroad and entrenchment of privileges at home.” Both sides were able toclaim that such atrocities were committed to promote the “national securitywhich was threatened by the other side.” ...